Sistem Informasi Absensi Siswa Berbasis Web di SMKS Teladan Pematangsiantar - Istiqomah Istiqomah; Priti Rindi Artika; M. Fakhriza; Pitta Emma Sitorus (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2024)
In the current digital era, the use of information technology is very important to increase efficiency and convenience in various fields. This research aims to develop and implement a web-based student attendance information system at Teladan Pematangsiantar Vocational School. This system is designed to increase the efficiency and accuracy of the student attendance process. The system development methodology uses a literature review approach, needs analysis, system design, implementation and evaluation. This system utilizes web-based technology to provide access to real-time attendance databases, allowing for more efficient monitoring by school staff. Evaluation is carried out by involving the participation of students and school staff in using the system. This research makes a positive contribution to managing student attendance at Pematangsiantar Teladan Vocational School, by providing an efficient and integrated solution.